A Study of The Potential Relationship between COVID-19 (Corona Virus) Daily Outbreak and Temperature Changes in Iran During March 2020 - Ali Mohammad Khorshiddoust; Sapna Tajbar; Mozaffar Faraji; Gholam Hassan Mohammadi (Iranian Journal of Health, Safety and Environment, 2022)
Climate is one of the most important structural factors on planet Earth and it is undoubtedly natural and all manifestations are at a wide range of levels. To recognize, control and adapt it, scientists have tried to improve life and well-being under various climatic conditions. Decreasing ambient temperatures can be common or annihilated by various diseases. The aim of this study is to investigate the possible relationship between covid-19 (Corona virus) disease and temperature fluctuations in Iran during March 2020. This is, of course, a preliminary study, and further research may explore other aspects of the subject. The methodology applied was the chi-square statistic to evaluate the test of independence between the studied variables and linear regression analysis to find the possibility of the influence of temperature as an independent climatic factor in the increase or decrease of the number of patients. In case of failure of linear regression analysis, the quadratic fit estimation was used. Results of this study proved the slight significant correlation between the occurrence of Corona and the temperature changes in the study area during March 2020. Although the temperature element is considered to be an influential climatic factor in Corona-like diseases such as influenza or SARS, this study could not profoundly prove such a relationship. The prevalence of Corona in Iran can be affected by several other factors such as deficiency of medical equipment, the behavior of the Iranian people towards the epidemic and the spread of this virus, socio-political and cultural gatherings.